Determination of attitudes and practices of nurses working in the psychiatry clinic towards physical health care of individuals with severe mental illness - Kurtoğlu, Hande Yardımcı; Çelik İnce, Sevecen (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Individuals with severe mental illness experience more physical health problems than the general population and their life expectancy may be shorter. Therefore, the physical care provided to these patients is very important.This study aims to examine the attitudes, practices, and training needs of nurses working in psychiatry clinics towards physical health care of individuals with severe mental illness. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This descriptive, cross-sectional study collected data from 139 nurses in psychiatry clinics using the Personal Information Form and Physical Health Attitude Scale. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. This study found that nurses often provide physical healthcare as part of their routine care for individuals with severe mental illness. However, the study also revealed that nurses require additional education to better provide this type of care. Despite this, the nurses generally displayed a positive attitude towards physical health. The average total score on the physical health attitude scale was 80.33±10.14. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The study concluded that nurses have a positive attitude towards physical health in general. The role of nurses working in psychiatry clinics is crucial in evaluating and caring for physical health of individuals with severe mental illness, as it is an important aspect of holistic nursing care. It is necessary to make nurses aware of their shortcomings in providing physical health care and support them in improving in this area.